Utility of Expert Panel to Identify Preventable Perinatal Deaths: Results from Audit Based Interventional Study in Two Districts of Karnataka State, India - H N, Harsha Kumar; Baliga, Shantaram B; Kushtagi, Pralhad; Kamath, Nutan; Rao, Sucheta S (National Journal of Community Medicine, 2023)
Background: India has child death review which misses the information from private hospitals and community. Community based perinatal death auditing is required to identify preventable perinatal deaths. The objectives are to know utility of expert panel in an audit-based approach to identify 1). preventable perinatal deaths, 2) Risk factors in cases of perinatal deaths Methodology: Perinatal death auditing was conducted in two districts of Karnataka state. As a part of audit system, an expert panel consisting of paediatricians and obstetricians was formed for each district. The panel met every month and received information about perinatal deaths occurring in the hospitals (government and private) apart from the community in these districts. The panel considered available information about survival chances and care provided to decide if a perinatal death was preventable, possibly preventable or not preventable. Results: Proportion Of identified preventable and possibly preventable perinatal deaths in Koppal District (60%, 20%) was higher than Dakshina Kannada district (34.4%, 30.2%). The proportion preventable intranatal and neonatal risks in Koppal District (79%, 66%) was higher than Dakshina Kannada District (47%, 19%). Conclusion: Expert panel is useful to identify preventable perinatal deaths. The pattern of risk identified has implications for improvements in quality of care provided to high-risk cases.